2013
DOI: 10.1111/exd.12137
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin inhibits UVB‐induced matrix metalloproteinase‐1/3 expression by suppressing the MAPK‐p38/JNK pathways in human dermal fibroblasts

Abstract: oxide could be supplied to the local wound area through the systemic blood circulation because topical tacrolimus does not reduce blood nitric oxide level.In conclusion, topically-treated tacrolimus does not have a negative effect on wound healing. Acknowledgements Conflict of interestsThe authors declare no conflict of interest. References1 Liu J, Albers M W, Wandless T J et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 16 publications
(21 reference statements)
0
38
0
Order By: Relevance
“…PPAR-γ ligand rosiglitazone (Sigma-Aldrich, USA) was dissolved in DMSO and added to cultured cells to the final concentrations of 5, 10, 20, and 40 μM as described previously (Hogan et al, 2011). Curcumin (Sigma-Aldrich, USA) was prepared in the same manner and added to cultured cells to the final concentrations of 5, 25, and 50 μM as described previously (Hwang et al, 2013). Recombinant mouse TGF-β2 (R&D Systems, USA) was used at a final concentration of 10 ng/ml as described previously (Ma et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…PPAR-γ ligand rosiglitazone (Sigma-Aldrich, USA) was dissolved in DMSO and added to cultured cells to the final concentrations of 5, 10, 20, and 40 μM as described previously (Hogan et al, 2011). Curcumin (Sigma-Aldrich, USA) was prepared in the same manner and added to cultured cells to the final concentrations of 5, 25, and 50 μM as described previously (Hwang et al, 2013). Recombinant mouse TGF-β2 (R&D Systems, USA) was used at a final concentration of 10 ng/ml as described previously (Ma et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…These bioactive compounds continue to gain popularity based on their several advantages, which include often having fewer side effects, showing better patient tolerance, and being relatively less expensive and acceptable due to a long history of use compared to synthetic ingredients [5]. In the search for effective drug leads from herbs used against skin abnormalities, bioactive compounds such as aloin [6], curcumin [7], resveratrol [8], gallic acid [9], quercetin, genistein and catechins [10] have been found.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of diabetic rats, MMP9 gene expression was found to be activated by the loss of H3K9me2 and the increase of H3K9ac at the NFκB binding site in the MMP9 promoter (6). The role of histone modification changes in regulating the response of dermal fibroblasts to UVR is not understood as well as the regulation of MMPs by UVR-induced signal transduction pathways and transcription factors (7). Epigenetic responses to UVR may contribute to the up regulation of MMPs, matrix remodeling, and photoaging.…”
Section: Introductionmentioning
confidence: 99%